THE RELATIONSHIP BETWEEN FAMILY HYGIENE PRACTICES AMONG FISHING HOUSEHOLDS AND STUNTING AMONG UNDER-FIVE CHILDREN IN PADANG SEURAHET VILLAGE - Rupiana; Teungku Nih Farisni; Fakhrurradhi Luthfi; T. Alamsyah; Yulizar (PT. Radja Intercontinental Publishing, 2025)
Stunting remains a major public health problem in Indonesia, particularly in coastal areas where family sanitation and hygiene conditions are inadequate. Padang Seuraheut Village, Johan Pahlawan Subdistrict, West Aceh, is a coastal area predominantly inhabited by fishing families with limited environmental sanitation, restricted access to clean water, and suboptimal hygiene practices. This study aimed to analyze the relationship between family hygiene practices and the incidence of stunting among under-five children in the village. This study employed a quantitative approach with a cross-sectional design and was conducted from August to December 2025. The study population comprised all children aged 12–59 months totaling 1,442, with a sample of 94 children selected using simple random sampling. Data on family hygiene practices were collected through mothers as respondents using questionnaires and observation checklists. Data were analyzed using the Chi-Square test. The results showed that all hygiene and sanitation variables were significantly associated with the incidence of stunting (p < 0.05). Poor handwashing practices with soap were strongly associated with stunting (100%), as were inadequate latrine conditions (75.0%), unhygienic food storage and preparation (76.6%), and improper waste and wastewater disposal (73.1%). These findings indicate that family hygiene practices and environmental sanitation play a substantial role in increasing the risk of stunting among under-five children. Improvements in sanitation facilities, family hygiene education, and community-based interventions in coastal areas should be prioritized as strategic measures for stunting prevention.